2012
DOI: 10.1158/0008-5472.can-11-3027
|View full text |Cite
|
Sign up to set email alerts
|

MiR-155 Is a Liposarcoma Oncogene That Targets Casein Kinase-1α and Enhances β-Catenin Signaling

Abstract: Liposarcoma can be an aggressive, debilitating and fatal malignancy. In this study, we identifed microRNAs (miRNAs) associated with the differentiation status of liposarcoma to gain insight into the basis for its progression. miRNA expression profiles determined in human tumors and normal fat specimens identified a de-differentiated tumor expression signature consisting of 35 miRNAs. Deregulated miRNA expression was confirmed in a second independent sample cohort. The miR-155 was the most overexpressed miRNA a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
98
1
5

Year Published

2014
2014
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 47 publications
(63 reference statements)
7
98
1
5
Order By: Relevance
“…Recently, several lines of evidence have purported to study the drug resistance and invasion/metastasis as a single entity. It was reported that miRNAs can regulate the expression of certain proteins and genes, which function as tumor suppressors or oncogenes in the occurrence and development of tumor MDR and metastases (31)(32)(33). Our current study elucidated that miR200c was downregulated in MDR cells compared with the parent cells, and a similar phenomenon also occurred in clinical recurrent and metastatic tumors.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, several lines of evidence have purported to study the drug resistance and invasion/metastasis as a single entity. It was reported that miRNAs can regulate the expression of certain proteins and genes, which function as tumor suppressors or oncogenes in the occurrence and development of tumor MDR and metastases (31)(32)(33). Our current study elucidated that miR200c was downregulated in MDR cells compared with the parent cells, and a similar phenomenon also occurred in clinical recurrent and metastatic tumors.…”
Section: Discussionsupporting
confidence: 53%
“…Until recently, CK1α was considered to be a "rogue" kinase (36), as its catalytic activity appears to be unregulated. However, fresh perspectives on the regulation of CK1α were gained in two recent studies, one showing CK1α protein expression to be downregulated by miR-155 in liposarcoma (53) and the other identifying a subset of the DDX family of RNA helicase as essential kinase-stimulatory cofactors of multiple CK1 isoforms, including CK1α (36). We demonstrate that oncogenic RAS, via its PI3K/ AKT/mTOR effector pathway, can also increase CK1α protein abundance and function.…”
Section: Discussionmentioning
confidence: 76%
“…The overexpression of miR-142 has been shown to inhibit the proliferation and colony-forming ability of primitive hematopoietic cells (31). Some of these functions appear to depend on the cellular type and context, since it was reported that miR-142 acts as an anti-migratory factor in hepatocellular carcinoma cells (32) and has also been reported to be deregulated in mesenchymal tumors (33). In the present study, demethylation agents induced Saos-2 and MG63 cell cycle arrest, thus inducing an increase in G 2 phase cells with a concomitant decrease in S phase cells.…”
Section: Discussionmentioning
confidence: 99%